Rola i znaczenie podstaw przedsiębiorczości w kształceniu ogólnym - Tracz, Mariola (Przedsiębiorczość - Edukacja, 2006)
The goal of this article is to take into consideration the role of the basis of entrepreneurship in the educational system. Author gives particular attention to EU educational strategy, which presumes the entrepreneurship is essential skill for young people to function in the knowledge society and on new job markets. The necessity of promoting the view that the entrepreneurship prepares for self-employment was indicated in European field of education. The entrepreneurship is one of five key subjects, by which European educational system, related to EU project on employment and unemployment, is implemented. Furthermore author presents how important the subject is for the personal and social development of students.